2019
DOI: 10.4317/medoral.22966
|View full text |Cite
|
Sign up to set email alerts
|

Stomatological disorders in older people: An epidemiological study in the brazil southern

Abstract: BackgroundThe aim of this retrospective, cross-sectional and observational study was to perform a survey of the stomatological conditions of elderly patients seen in a period of 40 years at a Stomatology Service in Southern Brazil.Material and MethodsA total of 24,347 medical records were reviewed, of which 5,063 belonged to elderly patients aged 60 to 97 years. The stomatological conditions, systemic conditions, and smoking and alcohol drinking habits as well were recorded.ResultsThe mean age of the patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 18 publications
0
5
0
3
Order By: Relevance
“…Para la comparativa con nuestro estudio que aporta una prevalencia de 0,84 casos por cien habitantes, y una reciente revisión sistemática (4) realizamos una revisión narrativa de la literatura. Seleccionamos 17 estudios (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) por el proceso metodológico en su desarrollo y la cantidad de citas generadas, según la página Web of Science.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Para la comparativa con nuestro estudio que aporta una prevalencia de 0,84 casos por cien habitantes, y una reciente revisión sistemática (4) realizamos una revisión narrativa de la literatura. Seleccionamos 17 estudios (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) por el proceso metodológico en su desarrollo y la cantidad de citas generadas, según la página Web of Science.…”
Section: Discussionunclassified
“…Siete son estudios de nuestra revisión de prevalencia desarrollados en un entorno clínico (25)(26)(27)(28)(29)(30)(31), en los que la prevalencia oscila entre 0,12% y 14,91 %. Los datos de prevalencia que aportan los estudios clínicos son de tipo retrospectivos, se recolectan de bases de datos, de historias clínicas, de casos ya diagnosticados de SBA, lo que posiblemente pueda limitar los resultados, ya que en algunos estudios (3,21) muchos de los pacientes tenían patologías orales como atrofia de las papilas linguales, lengua fisurada, estomatitis por dentadura postiza y candidiasis, que podrían explicar el síndrome de SBA.…”
Section: Discussionunclassified
“…This study included clinical‐based studies and population‐based studies. The clinical patients, we included mainly came from the department of oral medicine, department of oral pathology and maxillofacial surgery, and oral medicine was indicated as optimal when compared to other dental specialties ( Brailo et al., 2006; Fattori et al., 2019; Li et al., 2015; Netto et al., 2011). The data in clinical settings revealed that BMS patients had a high demand for medical consultation and further management (Xiao et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Another cross‐sectional study conducted in Sweden showed a prevalence of BMS of 3.7% among total of 1,427 adults between the ages of 20 and 69 (Bergdahl et al., 1999). While it raised up to 15% in a clinical‐based retrospective study from Brazil (Fattori et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In China, the percentage of people in China aged 60 years or over is rising dramatically [1]; persons of increasing age are more likely to suffer from various oral problems [2]. At present, though a certain proportion of oral mucosal diseases (OMD) does not need active treatment, but there is some evidence that people with oral diseases are associated with various negative outcomes, such as poor quality of life, a heavy global burden on social and economic health, high risk of disability, and impaired physical function [3,4], particular in the elderly [5,6].…”
Section: Introductionmentioning
confidence: 99%